2022
DOI: 10.1029/2021gl097703
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Atmospheric Evaporative Demand Is Increasing Flash Droughts in Spain During the Warm Season

Abstract: Flash droughts are characterized by rapid development and intensification, generating a new risk for drought impacts on natural and socio‐economic systems. In the current climate change scenario, the meteorological drivers involved in triggering flash droughts are uncertain. We analyzed the role of meteorological drivers underlying the development of flash droughts in Spain over the last six decades, evidencing that the effect of atmospheric evaporative demand (AED) on flash drought is mainly restricted to wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…It has destructive impacts on agricultural and ecological systems and leaves little time for drought preparation and mitigation, such as the 2012 flash drought in the US (Otkin et al., 2016), the 2019 flash drought in the South China (Y. Wang & Yuan, 2021), the 2010 flash drought in Russian (Christian et al., 2020), and the 2019 flash drought in Australia (Nguyen et al., 2021). This disaster has caused severe economic and agricultural losses in many parts of the world, the study of flash drought under climate change has aroused widespread concerns in recent decade (Mishra et al., 2021; Noguera et al., 2022; Yuan et al., 2019). David et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has destructive impacts on agricultural and ecological systems and leaves little time for drought preparation and mitigation, such as the 2012 flash drought in the US (Otkin et al., 2016), the 2019 flash drought in the South China (Y. Wang & Yuan, 2021), the 2010 flash drought in Russian (Christian et al., 2020), and the 2019 flash drought in Australia (Nguyen et al., 2021). This disaster has caused severe economic and agricultural losses in many parts of the world, the study of flash drought under climate change has aroused widespread concerns in recent decade (Mishra et al., 2021; Noguera et al., 2022; Yuan et al., 2019). David et al.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, flash droughts show wide spatiotemporal variability and remarkable seasonal differences [1] . Thus, flash drought in Spain may occur in any season associated with different meteorological drivers [ 7 , 8 ], causing diverse impacts. For these reasons, there is a need for flash drought monitoring and early warning in Spain.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Analysis of both historical data and model projections, globally and regionally, largely find trends toward increasing flash drought frequency (Christian et al, 2021;Mahto & Mishra, 2023;Sreeparvathy & Srinivas, 2022;Yuan et al, 2019). These broader trends are attributed, in part, to anthropogenic climate change, as well as consistent projected increases in evaporative demand combined with variable, but mostly small, projected changes in global precipitation (Christian et al, 2021;Mishra et al, 2021;Noguera et al, 2022;Yuan et al, 2019;Yuan et al, 2023). For example, Mishra et al (2021) attributed the projected increased flash drought frequency in India to increased intraseasonal variability of the monsoon, with increased flash drought risk following failed or delayed monsoon onset.…”
Section: Flash Drought In a Changing Climatementioning
confidence: 98%
“…The warming global climate has also created a growing need for better consideration of temperature and evaporative demand on drought development (Stagge et al, 2017) and increasing temperatures have been shown to affect flash drought characteristics in many regions (Noguera et al, 2022;Yuan et al, 2023). However, as with evaporation and ETbased indicators, SPEI has the potential to misestimate drought intensity and duration if the demand part of the equation is unrealistic or not properly calibrated (Park et al, 2018).…”
Section: Precipitation Indicatorsmentioning
confidence: 99%